2011
DOI: 10.1158/0008-5472.sabcs11-p2-14-07
|View full text |Cite
|
Sign up to set email alerts
|

P2-14-07: Ethnic Differences in Breast Cancer Molecular Subtypes and Survival Outcomes in a Multi-Ethnic Singaporean Population.

Abstract: Background: Previous studies have described differences in breast cancer biological subtypes from various ethnic backgrounds such as women of African descent. Data on the heterogeneity of breast cancer biology among Asian ethnic groups is limited. Objectives: The aim of this study was to evaluate the frequency of the different immunohistochemical (IHC) subtypes of breast carcinoma and clinical outcomes among Chinese, Malay and Indian patients (pts) at a single Singaporean institution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Conversely, TNBC is less common in Chinese/East Asians, with similar or lower frequency than NHW. 34 , 35 , 36 , 37 These discrepancies were also seen in women <40 years of age who do not routinely undergo BC screening, and hence not subjected to selection bias with overdiagnosis of hormone receptor-positive HER2-negative BCs. 36 , 37 …”
Section: Outcomes and Standard Clinicopathological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, TNBC is less common in Chinese/East Asians, with similar or lower frequency than NHW. 34 , 35 , 36 , 37 These discrepancies were also seen in women <40 years of age who do not routinely undergo BC screening, and hence not subjected to selection bias with overdiagnosis of hormone receptor-positive HER2-negative BCs. 36 , 37 …”
Section: Outcomes and Standard Clinicopathological Characteristicsmentioning
confidence: 99%
“…Ethnic groups with worse cancer survival outcomes are often the groups for whom obesity and related comorbidities are more prevalent. 13 , 15 , 23 , 35 The preliminary analysis of race and outcomes in the RxPONDER trial provided insight into this important issue. The percentage of patients with BMI 35 kg/m 2 and above ranged from 2% in Asians, 16% in Hispanics, 18% in NHW, 27% in Native Americans/Pacific Islander (NAPI), to 35% in blacks.…”
Section: Bmi and Comorbidities Lifestyle/environmental Factors And Al...mentioning
confidence: 99%
“…1 Approximately 20% to 25% of invasive breast cancers in Singapore are HER2 positive as defi ned by either immunohistochemistry (IHC) or fl uorescence in-situ hybridisation (FISH). 2,3 HER2 positivity is an independent prognostic marker of increased risk of disease recurrence and mortality. 2,4 Older studies have reported that even for small node negative HER2 positive breast cancers measuring 1 to 10 mm in size, distant recurrence risk can be as high as 15% to 30%, [5][6][7][8] although these studies did not distinguish outcomes between T1a (1 to 5 mm) and T1b (>5 to 10 mm) tumours.…”
Section: Introductionmentioning
confidence: 99%